2020
DOI: 10.1027/1864-9335/a000416
|View full text |Cite
|
Sign up to set email alerts
|

Contact With Gay Men and Lesbian Women Moderates the Negative Relationship Between Religiosity and Endorsement of Same-Sex Unions’ and Families’ Rights

Abstract: Abstract. This study investigated the moderation effect of contact with gay men and lesbian women on the relationship between religiosity levels with the endorsement of same-sex unions’ and families’ rights. Analyses were carried out on a national representative cross-sectional sample of 5,544 Italian adult residents (% females = 54). Multiple linear regressions coupled with an examination of the interaction between contact and religiosity showed that contact mitigated the negative relationship between religio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…One possibility, therefore, is that some individuals are attracted to conservative political perspectives primarily because of their personal stance against sexual minorities, whereas expressed beliefs of TMI emphasizing antifemininity may not be as relevant to these individuals. Given the links between religiosity and negative attitudes toward sexual minorities (Piumatti & Salvati, 2020), as well as the confluence of political conservatism and evangelical Christianity (Steensland & Wright, 2014), future researchers should consider extending the present model to include religious variables as potential moderators of the links between negativity toward sexual minorities and political conservatism.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility, therefore, is that some individuals are attracted to conservative political perspectives primarily because of their personal stance against sexual minorities, whereas expressed beliefs of TMI emphasizing antifemininity may not be as relevant to these individuals. Given the links between religiosity and negative attitudes toward sexual minorities (Piumatti & Salvati, 2020), as well as the confluence of political conservatism and evangelical Christianity (Steensland & Wright, 2014), future researchers should consider extending the present model to include religious variables as potential moderators of the links between negativity toward sexual minorities and political conservatism.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to criterion validity, previous literature found that several socio‐demographics (i.e. male gender, older people, low education), high religiosity, right‐wing political orientation, populist ideologies, right‐wing authoritarianism (RWA), high levels of social dominance orientation (SDO), dangerous world beliefs (DWBs), and competitive jungle beliefs (CJBs) predicted high levels of conspirative beliefs (Adam‐Troian et al, 2022; Douglas & Sutton, 2023; Pellegrini et al, 2019; Salvati et al, 2022) and sexual prejudice in heterosexual people (Adelman et al, 2021; Lingiardi et al, 2005; Piumatti & Salvati, 2020) and high levels of internalized sexual stigma in LGB people (Lingiardi et al, 2012; Salvati et al, 2019; Salvati & Chiorri, 2023; Salvati, Pistella, & Baiocco, 2018; Salvati, Pistella, Giacomantonio, & Baiocco, 2018). Thus, similarly, we expect that such predictors would associate with high levels in GILC scale, testifying a very good criterion validity.…”
Section: Introductionmentioning
confidence: 99%
“…More frequent contact with gays and lesbians is associated with greater support of their rights, including same‐sex marriage (Barth, Overby, & Huffmon, 2009; Hoffarth & Hodson, 2016). A more recent study carried out in Italy (Piumatti & Salvati, 2020) confirmed that contacts with LGB+ community positively related to the endorsement of same‐sex unions and families' rights, especially in participants with lower levels of religiosity.…”
Section: Introductionmentioning
confidence: 83%